A Case of Reactive Cervical Lymphadenopathy with Fat Necrosis Impinging on Adjacent Vascular Structures - Albert Y. Han; Jacob F. Lentz; Edward C. Kuan; Hiwot H. Araya; Mohammad Kamgar (Case Reports in Otolaryngology)
A tender neck mass in adults can be a diagnostic challenge due to a wide differential diagnosis, which ranges from reactive lymphadenopathy to malignancy. In this report, we describe a case of a young female with an unusually large and tender reactive lymph node with fat necrosis. The diagnostic imaging findings alone mimicked that of scrofula and malignancy, which prompted a complete workup. Additionally, the enlarged lymph node was compressing the internal jugular vein in the setting of oral contraceptive use by the patient, raising concern for Lemierre’s syndrome or internal jugular vein thrombosis. This report shows how, in the appropriate clinical context, and especially with the involvement of adjacent respiratory or neurovascular structures, aggressive diagnostic testing can be indicated.